The United Nations organization: safety and development - Mac Gregor, Felipe (1995)
The article focuses on the work of the United Nations in the light of what its Charter states in relation to international security and peace, and development. On the first point, the author mentions issues like military-backed political security, economic and social security, the abolition of the colonics, and human rights. The author goes on to track the progress of development, the UN's steps to promote it and its new perception, the components of which are intellectual understanding, moral commitment and effective political measures.